(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In India women are more in number than men. Dominant part of the women confronting some basic issues in their everyday life like sex separation in family, society, work place and so on. Government has executed a few strengthening modified to create or enable the women. Yet, they have not made any astounding improvement in their family and living conditions. It might be expected to the non-accessibility of education and learning on data about the rising technologies. Taught women impact all the relatives with whom they manage and it kills the poverty in this way activating improvement.